The Tension Between Legal Certainty and Justice in the Perspective of Legal Philosophy - Liliek Prisbawono Adi (Yuridika, 2026)
From the perspective of law enforcement, legal certainty and justice do not always complement each other; rather, they often stand in tension and may even contradict one another. When legal certainty is emphasized, justice may be postponed or compromised. Conversely, when law enforcement prioritizes justice, legal certainty can become weakened or overlooked. Nevertheless, these two principles are not inherently incompatible, as they can also function in a complementary manner within a balanced legal system. This article examines the tension between legal certainty and justice through the lens of legal philosophy. It explores the historical development of these concepts, beginning with Ancient Greek philosophy—particularly the ideas of Plato and Aristotle—through medieval thought, natural law theory, legal positivism, and contemporary legal theory. By analyzing the evolution of these philosophical traditions, this study seeks to demonstrate that the relationship between legal certainty and justice is dynamic and context-dependent. Ultimately, the article argues that an ideal legal system should strive to harmonize legal certainty and justice, ensuring both predictability in law and fairness in its application.